Securing Sahelian pastoralism by using a remunerated workforce for livestock keeping activities: The ambivalence of commodification - Wane, Abdrahmane; Touré, I.; Njiru, Nelly M.; Mballo, A.D. (EDP Sciences, 2018)
Sahelian pastoralists use mobility, diversification, and even pluriactivity as main adaptation strategies to the asymmetrical distribution of multifaceted resources. Complex relations vis-à-vis this risky environment hide slowing transitions from a traditional inward-looking to an outward-looking economy, which is characterised by increasing use of a remunerated workforce. The growing commodification of the economy of Sahelian pastoralists could generate new forms of uncertainty. The authors of this paper use a principal-agent model to analyse the remunerated workforce and demonstrate the mixed results of this strategy in the context of structural risk in the Sahel. The authors then highlight the conditions under which trust and reputation are developed to stabilise employment relations and better cope with and/or mitigate various shocks.